Effects of crop load on leaf physiological characteristics and yield of starfruit cultivated under protected structure - Mohd Fauzi R. (Malaysian Society of Plant Physiology, 2019)
A study was conducted to look at the effects of crop load on starfruit cultivated under protected structure. Increase in crop load resulted in increase in leaf physiological activities such as stomatal conductance and transpiration significantly. Yield of starfruit also increased significantly with increase in crop load from 21Kg/tree at the lowest crop load to 74Kg/tree at the highest crop load. The number of 'M' and 'S' grades fruit increased with increase in crop load.